ANALISIS PARTISIPASI AKTIF PESERTA DIDIK DALAM PEMBELAJARAN IPAS FASE B SEKOLAH DASAR DENGAN METODE GALLERY WALK - Izzaton Nisak, Qunita; Meirza Nanda Faradita; Holy Ichda Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the active participation of students in the Phase B elementary school IPAS learning using the gallery walk method. The type of research used in this study is descriptive qualitative. The data collection techniques in this study were conducted using observation, interviews, and documentation. Meanwhile, the data analysis techniques used by the researcher are data collection, data reduction, data presentation, and conclusion/verification. Based on the research that has been conducted, it was found that the gallery walk method can encourage the creation of interaction, collaboration, active participation, and understanding of the learning material among students. This method can also serve as an alternative means of active participation for students. Students show active involvement in group discussions, critical thinking skills, and active participation. This study recommends the implementation of the gallery walk method as an engaging and effective alternative learning strategy to optimize students' active participation.